Enhanced mechanical and thermal properties of hollow wood composites filled with phase-change material. (20th May 2020) - Qi, Chusheng; Zhang, Feng; Mu, Jun; Zhang, Yang; Yu, Zhiming
Abstract: To obtain lightweight wood building materials with good thermal insulation, energy-saving properties, and satisfying mechanical properties, low-density fiberboard and hollow wood composites (HWC) embedded polyvinyl chloride tubes were fabricated by hot-pressing. Polyethylene glycol was used as the phase-change material to fill polyvinyl chloride tubes and obtain phase-change hollow wood composite (PHWC). The physical and mechanical properties of HWC and PHWC were tested, and their thermal properties were analyzed and simulated. The results showed that the thermal conductivities of low-density fiberboard, HWC, and PHWC ranged from 0.06 to 0.07 W/(m·K), indicating they had sufficient physical and mechanical properties to be used as thermal insulation building materials. The combination of series and parallel models accurately predicted the thermal conductivity of HWC and PHWC, whose structures were similar to a series structure. The addition of polyethylene glycol into HWC allowed the PHWC to store latent heat and reduce indoor temperature fluctuations. Heat transfer simulations showed that when used as a non-structural building wall material, the PHWC wall had a better energy efficiency compared with a concrete wall. Thus, PHWC has potential applications as thermal insulation and phase-change building material. Graphical abstract: Image 1 Highlights: Lightweight hollow wood composites with a density of 0.3 g/cm 3 were fabricated. The thermal conductivity of lightweight hollow wood composites is 0.06–0.07 W/(m·K). Polyethylene glycol as a phase change material was added into hollow wood composites. Phase-change lightweight wood composites were better insulators than concrete.